Cardio-Oncology - Lipshultz, Steven E.; Franco, Vivian; Carver, Joseph; Minotti, Giorgio
The editorial mission of Cardio-Oncology is to advance the science and practice of this emerging field to find a balance between oncologic efficacy and reducing adverse cardiovascular effects through timely publication and dissemination of peer-reviewed research. As an open access, online journal Cardio-Oncology provides a high visibility platform for the publication of original research and expert reviews on the cardiovascular effects of cancer treatment. The journal welcomes submissions to the following sections: • Adult Oncology - Giuseppe Curigliano and Susan Dent • Clinical Cardiology - Daniela Cardinale and Daniel Lenihan • Clinical Trials - Michael S Ewer and Thomas Suter • Geriatric Oncology - Dawn L Hershman • Imaging - Steven Colan • Nursing - Anecita Fadol and Mary McCabe • Pediatric Oncology - Gregory Armstrong and Stephen E Sallan • Radiation Oncology - Louis Constine • Translational Cardiology - Bonnie Ky and Ed TH Yeh The journal welcomes submissions related to the pathophysiology, prevention, diagnosis, and treatment of the cardiotoxic effects of cancer therapies, from basic mechanistic studies, to translational, preclinical and clinical research, including clinical trials, outcomes studies, case reports, and imaging techniques. Conference proceedings or reports are also welcome. Topical areas include, but are not limited to: • Mechanisms of the cardiotoxicity of anticancer drugs • Biomarkers and the susceptibility of cancer patients to cardiovascular injury • Cancer treatment for patients with a cardiovascular history • Monitoring and detection of patients at risk of cardiotoxicity • Prevention and treatment strategies, such as dose changes for chemotherapy • Cardiovascular care for cancer survivors The only journal devoted exclusively to this emerging specialty, Cardio-Oncology provides an international forum for communicating the latest findings and state-of-the-art reviews, filling a critical gap in the science and clinical practice of this important field. The journal serves as essential reading for basic researchers, drug developers, adult and pediatric onco-hematologists, cardiologists, radiologists, surgical oncologists, internists, geneticists, epidemiologists, and other health care scientists and providers.